Analisis Pengaruh Pemasangan Kisi Beton (Concrete Crib) Sebagai Perkuatan Lereng Terhadap Kestabilan Lereng Dengan Menggunakan Metode Kesetimbangan Batas Di PT. Dairi Prima Mineral Kabupaten Dairi Provinsi Sumatera Utara - Wiwik Windasari B Manalu; Rizto Salia Zakri (Journals Mining Engineering : Bina Tambang, 2021)
PT. Dairi Prima Mineral is a company engaged in the field of mineral mining, this is in the form of zinc ore and black lead minerals whose mining locations are located in Sopokomil Village, Dairi Regency, North Sumatra. the mining system is carried out with an underground mining system. construction activities or preparation for mining activities, the most important thing to do during construction activities is to pay attention to the condition of the mining area, especially slope stability, PT. Dairi Prima Mineral carries out protection activities on the slopes, this is related to the long-term safety of the slope treatment, and plans to build processing plant facilities and other infrastructure under the foot of the slope or the toe which is 10 meters from the slope.The method used is the boundary equilibrium method (simplified Bishop). As a result of the research, it can be concluded several things, namely the slopes in area 8 in actual conditions using actual slope geometry data in the field as well as laboratory testing to obtain physical and mechanical properties of soil and rock and after that a modeling of the slopes is carried out to see the slope safety factor and simulation on the slopes. when the slope is given a concrete crib, for the actual condition the safety factor for single slopes is 1,271 natural conditions and saturated conditions 1,231, from the actual conditions the slopes are not stable so it is recommended to use a double bench with natural slope FK 1,429 and saturated 1,393, from the recommendation FK has not complied with SNI 8470-2017 FK≥ 1.5. Furthermore, the double bench slope was given anchor bolt reinforcement for stable slope conditions with FK 1,535 saturated conditions and natural conditions 1,601 with the number of anchors used 24 anchors and the distance between anchors 3 meters with a length of 9 meters, from safe slope modeling or slopes in a stable condition with FK 1.5 for permanent slopes and long term slopes.After it is known that slope reinforcement with retrofit planning using the previous reinforcement specifications in area 8 is very maximal and economical, it can be seen from slope analysis using the simplified Bishop boundary equilibrium method by getting FK≥ 1.5  Keywords: Analysis, Slope Reinforcement, Concrete Crib, Bishop's Method, Slope Geometry.